PERUMPAMAAN DALAM AL-QUR’AN (Amtsal) MENGUNGKAP MAKNA ABSTRAK MENJADI KONKRET - Annisa Azizah; Laelatul Musdallifah; Maulida Apriliatama; Savita Eka Fitria; Talita Zahra Karima; Akhmad Dasuki (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
This study examines the concept of Amtsal in the Qur’an as a rhetorical method used to clarify abstract meanings through concrete and relatable analogies. Using a library research approach, this study analyzes various scholarly sources, including journal articles, books, and academic documents, to explore the definitions, classifications, and rhetorical functions of Qur’anic Amtsal. The findings indicate that Amtsal plays a significant role in divine communication, as it bridges human understanding with metaphysical concepts, moral values, and spiritual teachings by presenting vivid symbolic imagery. The three main forms of Amtsal amtsal musyarrahah, amtsal kaminah, and amtsal mursalah demonstrate the Qur’an’s linguistic flexibility in conveying messages with varying levels of clarity and depth. This study concludes that Amtsal serves as an effective linguistic and pedagogical device that enhances comprehension, reflection, and internalization of Qur’anic messages.